KOREOGRAFI TARI BELAYIE KE LUBUK SAKTI DI DESA EMPELU KECAMATAN TANAH SEPENGGAL KABUPATEN BUNGO PROVINSI JAMBI - Nadya Putri Kinanti; Asriati, Afifah (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to reveal and describe the choreography of the Belayie Dance to Lubuk Sakti in Empelu Village, Tanah Sepenggal District, Bungo Regency, Jambi Province. This type of research is qualitative with a descriptive analytical method. The instruments of this study are the researchers themselves, assisted by writing tools and a mobile phone. Data was collected through literature studies, observation, interviews, and documentation. The steps to analyse the data are data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the choreography process of the Belayie Dance to Lubuk Sakti goes through four main stages: idea generation, exploration, improvisation, and composition. The idea for creating the dance originated from observations of the Belayie ritual, which were then developed through exploration of paddling movements, rain-requesting movements, village community activities, and the atmosphere of rainfall. Improvisation arises spontaneously from the choreographer's imagination regarding the life of the Empelu Village community, while the composition stage is carried out by arranging various movements, floor patterns, dynamics, music, and costumes to form a complete and meaningful performance. The choreography of the Belayie Ke Lubuk Sakti Dance is reviewed through the elements of choreography which include movement, overhead design, floor design, dramatic design, dynamics, group composition, music, and equipment such as makeup, costumes, and props. The movements depict expressions of supplication, togetherness, as well as community ritual activities. The floor patterns and group composition are arranged to display communal unity and the role of the village elders. The dramatic design of the Belayie Ke Lubuk Sakti Dance is a single cone dramatic design. The Belayie Ke Lubuk Sakti Dance uses several group designs including alternating floor designs, simultaneous, and split designs which create interesting movement variations and dynamics. The musical instruments used to accompany the Belayie Ke Lubuk Sakti Dance are wooden Kulintang, Doll, Tambourine, Guitar, Bass, Keyboard, Accordion, Violin, and Drum. The props used in the Belayie Ke Lubuk Sakti Dance include a boat, conical hat, and lantern.